Is There a Link Between Motor Performance Variability and Social-Communicative Impairment in Children With ADHD-CT: A Kinematic Study Using an Upper Limb Fitts' Aiming Task. (January 2015) - Papadopoulos, Nicole; Rinehart, Nicole J.; Bradshaw, John L.; Taffe, John; McGinley, Jennifer
Objective: This study investigated the relationship between motor performance and social-communicative impairment in children with ADHD-combined type (ADHD-CT).Method: An upper limb Fitts' aiming task was used as a measure of motor performance and the Social Responsiveness Scale as a measure of social-communicative/autistic impairment in the following groups: ADHD-CT ( n = 11) and typically developing (TD) controls ( n = 10).Results: Children with ADHD-CT displayed greater variability in their movements, reflected in increased error variance over repeated aiming trials compared with TD controls. Motor performance variability was associated with social-communicative deficits in the ADHD-CT but not in the TD group.Conclusion: Social-communicative impairments further complicate the clinical picture of ADHD-CT; therefore, further research in this area is warranted to ascertain whether a particular pattern of motor disturbance in children with ADHD-CT may be clinically useful in identifying and assessing children with a more complex ADHD presentation.